Examining Case Dismissal Outcomes in Prosecutor-Led Diversion Programs. (April 2023) - Epperson, Matthew W.; Sawh, Leon; Patel, Sadiq; Pettus, Carrie; Grier, Annie
Prosecutors' offices are a critical site for criminal legal reform and decarceration efforts. Prosecutor-led diversion programs (PLDPs) are a prosecutorial innovation that process cases away from punitive prosecution and, instead, offer various services and supports. Successfully completing a PLDP results in the dismissal of the charge, which helps participants to avoid formal entry into the criminal legal system and a range of collateral consequences. This paper reports findings from over 11, 000 participants in six PLDPs in three Midwestern jurisdictions, and examines race/ethnicity and charge characteristics associated with successful program completion and case dismissal. Findings indicate that PLDPs have the capacity to provide alternative processing to a large volume of defendants with high completion rates, although the likelihood of racial/ethnic minorities to successfully complete the program is mixed. PLDPs are discussed as a promising policy and programmatic innovation that can help to move away from an era of mass incarceration.